Intravenous versus intra-arterial digital subtraction angiography: Occlusion rate and complication assessment of experimental aneurysms after flow diverter treatment in rabbits. Issue 2 (April 2019) - Simgen, Andreas; Tomori, Toshiki; Bomberg, Hagen; Yilmaz, Umut; Roth, Christian; Reith, Wolfgang; Mühl-Bennighaus, Ruben
Purpose: Conventional intra-arterial digital subtraction angiography, which requires surgical exposure and ligation of the femoral or carotid artery, is a limited method of evaluating elastase-induced aneurysms in New Zealand white rabbits. The purpose of this study was to assess aneurysm morphology, occlusion rates and complications after flow diverter treatment comparing intravenous and intra-arterial digital subtraction angiography. Methods: We previously published a preclinical study in which we evaluated the occlusion rates of elastase-induced aneurysms after treatment with a prototype flow diverter, by using intra-arterial digital subtraction angiography at three months ( n = 9) and six months ( n = 9). In addition to that intravenous digital subtraction angiography before treatment, after one month (early follow-up group) and after three months (late follow-up group) was performed. Occlusion rates were compared within the two groups by means of residual contrast filling. Results: Baseline aneurysm characteristics revealed no significant differences between intra-arterial digital subtraction angiography and intravenous digital subtraction angiography. Aneurysm occlusion rates in both follow-up groups using intravenous digital subtraction angiography were significantly higher compared to intra-arterial digital subtraction angiography (early follow-up group: intravenous digital subtraction angiography (one month) versus intra-arterial digital subtraction angiography (three months); p = 0.03 and late follow-up group: intravenous digital subtraction angiography (three months) versus intra-arterial digital subtraction angiography (six months); p = 0.04). Intravenous digital subtraction angiography is feasible to detect and reproduce device occlusions, in-stent stenosis and post-stent stenosis. Conclusion: Intravenous digital subtraction angiography can not give a sufficient statement on the aneurysm occlusion process compared to intra-arterial digital subtraction angiography and is therefore not recommended for imaging follow-up after flow diverter treatment in rabbits. Regarding untreated aneurysms and complications like device occlusions, in-stent stenosis and post-stent stenosis intravenous digital subtraction angiography proofed to be a good alternative to intra-arterial digital subtraction angiography in our study.